Genes required for B cell development - Conley, Mary Ellen (American Society for Clinical Investigation, 2003)
Mutations in a variety of genes can cause congenital agammaglobulinemia and a failure of B cell development. The currently known genes encode components of the pre–B cell receptor or proteins that are activated by cross-linking of the pre–B cell receptor. Defects in these genes result in a block in B cell differentiation at the pro–B to pre–B cell transition. A patient with a translocation involving a previously unknown gene, LRRC8, demonstrated a block at exactly the same point in B cell differentiation (see the related article beginning on page 1707). It will be interesting to determine whether the protein encoded by this gene interacts with the pre–B cell receptor signal transduction pathway or is involved in a new pathway.